Immune-driven adaptation of hepatitis B virus genotype D involves preferential alteration in B-cell epitopes and replicative attenuation—an insight from human immunodeficiency virus/hepatitis B virus coinfection. (July 2015) - Mondal, R.K.; Khatun, M.; Ghosh, S.; Banerjee, P.; Datta, S.; Sarkar, S.; Saha, B.; Santra, A.; Banerjee, S.; Chowdhury, A.; Datta, S.
Abstract: An important driving force behind the sequence diversity of hepatitis B virus (HBV) is viral adaptation to host immune responses. To gain an insight into the impact of host immunity on genetic diversification and properties of HBV, we characterized HBV of genotype D from treatment-naive hepatitis B e antigen-positive (EP) and hepatitis B e antigen-negative (EN) patients with chronic hepatitis B (CHB), where HBV is under stronger immune pressure, with that of HBV derived from human immunodeficiency virus (HIV)/HBV-coinfected individuals, where HIV infection has significantly weakened the immune system. Full-length sequence analysis showed that HBV heterogeneity was most extensive in EN-CHB followed by EP-CHB and HIV/HBV coinfection. The relative magnitude of non-synonymous changes within B-cell epitopes was greater than that in T-cell epitopes of HBV open reading frames (ORFs) in both EP-CHB and EN-CHB. Nine amino acid substitutions were identified in B-cell epitopes and one in a T-cell epitope of HBV in EN-CHB, most of which resulted in altered hydrophobicities, as determined using the Kyte and Doolittle method, relative to wild-type residues found in HBV from the HIV-positive group. Additionally, 19 substitutions occurred at significantly higher frequencies in non-epitope regions of HBV ORF-P in EN-CHB than HIV/HBV-coinfected patients. In vitro replication assay demonstrated that the substitutions, particularly in reverse transcriptase and RNaseH domains of ORF-P, resulted in a decline in replication capacity of HBV. Hence, our results indicate that HBV adapts to increasing immune pressure through preferential mutations in B-cell epitopes and by replicative attenuation. The viral epitopes linked to immune response identified in this study bear important implications for future HBV vaccine studies.